BGT 313/3 – Agriculture, Forest And Stored Product Entomology [Entomologi Pertanian, Hutan Dan Hasil Simpanan] - Jun 2014 - PPSKJ, Pusat Pengajian Sains Kajihayat (2014)
Second Semester Examination Academic Session 2013/2014 June 2014 Duration: 3 hours